2016
DOI: 10.1371/journal.pone.0149072
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Reader Reliability of Early FDG-PET/CT Response Assessment Using the Deauville Scale after 2 Cycles of Intensive Chemotherapy (OEPA) in Hodgkin’s Lymphoma

Abstract: PurposeThe five point Deauville (D) scale is widely used to assess interim PET metabolic response to chemotherapy in Hodgkin lymphoma (HL) patients. An International Validation Study reported good concordance among reviewers in ABVD treated advanced stage HL patients for the binary discrimination between score D1,2,3 and score D4,5. Inter-reader reliability of the whole scale is not well characterised.MethodsFive international expert readers scored 100 interim PET/CT scans from paediatric HL patients. Scans we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 22 publications
4
32
0
7
Order By: Relevance
“…[19,20] In previous studies of response assessment using D5PS, few reported the interobserver agreement for all 5 points of the scoring method, and only a fair degree of agreement was observed with Cohen κ ranging from 0.13 to 0.387. [21,22] The dichotomization of the D5PS (score 1–3 vs score 4–5) produced higher agreement with Cohen κ ranging from 0.502 to 0.96. [19,21,23] Overall, the results of our study and previous studies show a wide range of interobserver agreement in qualitative PET analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] In previous studies of response assessment using D5PS, few reported the interobserver agreement for all 5 points of the scoring method, and only a fair degree of agreement was observed with Cohen κ ranging from 0.13 to 0.387. [21,22] The dichotomization of the D5PS (score 1–3 vs score 4–5) produced higher agreement with Cohen κ ranging from 0.502 to 0.96. [19,21,23] Overall, the results of our study and previous studies show a wide range of interobserver agreement in qualitative PET analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Deauville scale was introduced to standardize the response interpretation, resulting in good reliability in some hands (Baratto et al, 2018). However, others show that there is only moderate inter-observer agreement in response classifications despite this approach (Han et al, 2016;Kluge et al, 2016). The problem with poor response agreement between observers is that the full potential of the PET/CT technique is not used.…”
Section: Ai Versus Radiolmentioning
confidence: 99%
“…Однако оценка накопления глюкозы при этом методе является субъективной. Проведенное исследование, в котором 5 независимых экспертов оценивали результаты ПЭТ/КТ по 5-балльной шкале Deauville после 2 блоков ОЕРА (винкристин, этопозид, преднизолон, доксорубицин), показало, что только в 42 % случаев совпали результаты у 2 экспертов [12]. Таким образом, становится понятной необходимость создания референс-центров по пересмотру визуализации больных ЛХ.…”
Section: определение групп рискаunclassified